Bad girls of Japan - Miller, Laura, 1953-; Bardsley, Jan (Palgrave Macmillan, 2005)
Are bad girls casualties of patriarchy, a necessary evil, or visionary pioneers? By tracing the concept of the bad girl in Japan as a product of specific cultural assumptions and historical settings, Bad Girls of Japan maps new roads and old detours in revealing a disorderly politics of gender. The essays explore deviancy in richly diverse media. Mountain witches, murderers, performance artists, cartoonists, schoolgirls, and shoppers gone wild are all part of the terrain.